HUBUNGAN ANTARA PENGETAHUAN IBU NIFAS TENTANG PERSONAL HYGIENE PADA LUKA PERINEUM DENGAN PENYEMBUHAN LUKA FASE PROLIFERASI DI WILAYAH KERJA PUSKESMAS JENGGOT KOTA PEKALONGAN TAHUN 2013 - Siti I'anah; Mardi Hartono; Supriyo . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
One of the causes of postpartum maternal death is if the infection does not get help, can progress to sepsis. The support factors infection genetalia in the community among many others puerperal women  do  not  pay  attention  to  hygiene  in  the  injured  area  perineumnya,  because  to  puerperal women, especially from the middle and lower economic circles have less knowledge in performing personal hygiene. Knowledge of the importance of personal hygiene in the perineal wound is very supportive  of  the  wound  healing  process  so  that  the  infection  can  be  avoided.  This  study  was conducted to determine the relationship between postpartum  maternal  knowledge about personal hygiene  with  the  proliferative  phase  of  wound  healing  in  Community  Health  Centre  Jenggot Pekalongan  in  2013.  This  research  uses  a  descriptive  design  with  cross  sectional  correlation. Sampling  was  carried  out  by  means  of  the  total  population  that  is  all  postpartum  women  with perineal  wound  suturing  is  done  well  or  not  done  or  not  done  suturing  to  40  people  5-20  days postpartum mothers. Collecting data using a questionnaire. Analysis of data used to test bivariate analysis  spearmen's  Rank.  These  results  indicate  that  the  respondent  has  knowledge  of  personal hygiene in  good perineal  wound 18 people (45.0%), sufficient knowledge of 18 people (45.0%), experienced a proliferation phase of wound healing, (ρ: 0.006 <α 0.05 ) This shows that there is a relationship between knowledge of the proliferative phase of wound healing. The conclusion that can be drawn is that there is a relationship between postpartum maternal knowledge about personal hygiene  in  the  perineal  wound  with  the  proliferative  phase  of  wound  healing.  It  is  therefore expected  to  continue  to  support  new  mothers  of  activities  performed  by  midwives,  especially counseling about personal hygiene during parturition with a midwife went to get more information about personal hygiene in the perineal wound.Keyword  :Konowledge, personal hygiene, the proliferative phase of wound healing Library    :19 books (2002-2012), 3 websites, 4 journal, scientific papers 1